Economic reforms and manufacturing productivity: Evidence from India - Saibal Ghosh (Economics and Econometrics Research Institute (EERI), 2010)
Using data on 2-digit industry for 1981-2004, the study examines the association between growth in total factor productivity and economic reforms. Accordingly, we first compute industry-level productivity growth using advanced econometric techniques and thereafter ascertain the time frame over which economic reforms impact productivity. The evidence suggests that productivity growth is not reliably higher after reforms than prior to reforms. In addition, the findings indicate that it is primarily the interest rate channel that is important in explaining changes in productivity. Among macroeconomic policies, trade reforms and industrial delicensing appear to be instrumental in explaining productivity changes.
Keywords: D24; L60; O47; 330; Economic reforms; total factor productivity; Levinsohn Petrin; Indian manufacturing